PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN WISATA ALAM BUKIT SULAPA ANGIN PUNJABU DESA BUNTU BUANGIN KABUPATEN SIDRAP - Kafrawi, Muh; Mappamiring, Mappamiring; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aimed to find out how the form of participation of the community's personnel and materials in Buntu Buangin Village, Sidrap Regency. The number of informants in this study were 7 people. This study used a qualitative descriptive type of research. Data collection techniques were observation, interviews, and documentation. The results of this study indicated that empowerment in terms of 1) the form of participation of community workers in Buntu Buangin Village run optimally, it  seen that they were active in managing an existing natural resource, 2) the form of material participation of the community in Buntu Buangin Village was carried out well, because the community was  very enthusiastic about providing various kinds of assistance in order to complete the Buntu Buangi Punjabu tourist spot, as for the forms of assistance provided such as assistance with construction tools. 3) the form of community fund participation in Buntu Buangin Village was carried out well, because the community was very enthusiastic about providing various kinds of assistance. as for the form of assistance provided such as assistance in the form of money, but providing assistance in the form of food, drinks, and cigarettes for the workers.